Rancangan Sistem Cash flow Statement Berbasis Web Pada Clarity&Fluency School Of English - Meri Mayang Sari; Citra Marina; Andrianes Andrianes (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2020)
Clarity & Fluency School of English is one of the businesses in the field of education with the type of English courses and Tutoring. Every business, both agency and individual, cannot be separated from information needs. The data needed in the form of accounting information in the form of financial statements. In an age where information needs more rapidly then needed analysis of a system according to requirement. Reporting activity is the most important aspect in companies or government agencies because any expenditure and cash receipts made by companies or government agencies should be made a report for decision making. In the Clarity & Fluency School of English cash flow statement, both cash receipts and disbursements still use office applications, namely Microsoft Excel. the method used in this study uses the SWOT analysis method, PHP as the programming language and MySQL as the database. Meanwhile, the data obtained were analyzed and illustrated using UML (Unified Modeling Language)